(untitled) (Scientific Journal of Research Studies in Future Human Sciences, 2024)
This Article examines the role of NATO’s eastern flank in the Middle East, emphasizing that countries enter into alliances in order to protect their common interests. NATO, which was initially formed as a regional military alliance, was restructured by the United States after World War II to respond to its security needs and interests in Western Europe and the Mediterranean. Today, one of NATO’s main challenges is whether it should take on greater global responsibilities in the face of new threats emerging beyond the European continent. This study specifically examines how to build new relationships with potential partners and how to encourage NATO’s Eastern flank to take on more responsibilities in the Middle East. In order to answer this question, two countries from NATO’s Eastern flank, the Czech Republic and Poland, have been selected. These two countries are analyzed as representatives of different regions on NATO’s Eastern flank in order to achieve greater diversity in the regional analysis. The current Ukrainian crisis has had a significant impact on NATO and has defined a new and simpler task for it: deterrence and defense of the Eastern flank against Russian threats. The strategic interests of Poland and the Czech Republic in the Middle East are examined as the first variable in this study; because if these countries have no desire or ability to gain interests in the Middle East, their importance decreases. The second variable is the level of participation of the Czech Republic and Poland in the Middle East, which analyzes the interactions of these countries in this region.